Comparative Study Of Dynamic Earthquake Analysis With Spectral Design And Time History Methods - Nugraha Eka Saputra; Yulita Arni Priastiwi (Jurnal Indonesia Sosial Teknologi, 2023)
Earthquakes are natural events that cannot be prevented by humans and their occurrence is very difficult to predict. In civil engineering, especially in the structural field, earthquake loads are a major problem in planning economical and safe building structures. This study aims to determine the comparison of earthquake structures with the Response Spectrum, Response Spectrum Matched, Time Histories, and Time Histories Matched methods on the magnitude of the natural vibration period of the structure, the basic shear force, mass participation, displacement, and deviation between levels. The results of this study that the period of natural vibration of the structure with the earthquake method RS 1.412 seconds, RSM 1.453 seconds, TH 1.453 seconds, and THM 1.453 seconds is between the lower limit of 1.054 seconds and the upper limit of 1.476 seconds, so it meets the requirements of SNI 1726:2019. The results of the base shear analysis showed that dynamic analysis is greater than static and the structural model meets the requirements that VDynamics > 100%. VStatic. The results of the analysis of building mass participation in various earthquake methods meet the provisions with results of more than 90%. The results of the analysis of displacements are obtained for the x-direction, the largest THM is 41.945 mm and for the y-direction, TH is 57.330 mm. The results of the drift ratio analysis are obtained for the results of the y-direction drift which is greater than the x-direction drift and permit control for all earthquake methods is safe and meets the requirements of SNI 1726:2019.